Mejoramiento genético. Mejoramiento de caracteres. Tolerancia a suelos ácidos - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
The CIAT agronomy-soils subprogram, carried out in Quilichao, Colombia, emphasized the screening of varieties for tolerance to high Al and/or low available soil P, and the design of expt. to better understand the physiological mechanisms involved in these tolerances. Another screening expt. for P efficiency was planted in Popayan (Colombia), and in Brazil CIAT carried out acid soil tolerance and root studies. The yields of the best performing var. under P and Al stress are presented in table form as well as the preliminary results of trials in Brazil. (CIAT)